Impact of restorative material on fracture behaviors of class II restoration in endodontically treated deciduous molars - Wada, Kanae; Wada, Junichiro; Uctasli, Mine Betul; Uctasli, Sadullah; Yavuz, Yasemin; Iwamoto, Tsutomu; Vallittu, Pekka K.; Garoushi, Sufyan; Lassila, Lippo (Japan, 2025)
The purpose of this study was to investigate the fracture behavior of endodontically treated (ET) deciduous molar when directly restored with different restorative materials in Class II (MO) cavities in comparison with permanent teeth. MO cavities were prepared with 2.4-2.5 mm and 1.9-2.0 mm in buccolingual width, and mesiodistal width of each cavity walls, respectively, followed by direct restoration with different materials: resin-modified glass ionomer cement (RMGIC), composite resin (CR), and composite resin containing 25% short glass-fiber (SFRC). All specimens were subjected to mechanical loading tests at a speed of 1 mm/min and evaluated fracture resistance and fracture modes. A one-way ANOVA followed by a Tukey multiple comparisons analysis was used. Deciduous-SFRC (3,310.5±396.2 N) were significantly higher fracture resistance than permanent-RMGIC (1,633.8±346.8 N) (p<0.001), and permanent-CR (1,400.0±381.3 N) (p<0.001). For the direct restoration of MO cavity after endodontic treatment, SFRC demonstrated its promising performance in load-bearing capacity and failure mode, especially in ET deciduous molars.